(untitled) (International Journal of Engineering and Computer Science, 2018)
Multilevel inverters have become more attractive for researchers due to low total harmonic distortion in the output voltage and low electromagnetic interference. This paper proposes a novel single-stage quasi-cascaded H-bridge five-level boost inverter. The proposed quasi cascaded h-bridge five-level boost inverter has the advantages over the cascaded H-bridge quasi-Z-source inverter in cutting down passive components. Consequently, size, cost, and weight of the proposed inverter are reduced. A capacitor with low voltage rating is added to the proposed topology to remove an offset voltage of the output AC voltage when the input voltages of two modules are unbalanced. Besides, sinusoidal pulse width modulation techniques used here. PID controller is used to control the capacitor voltage of each module. This paper presents circuit analysis, the operating principles, and simulation results of the proposed system